Dawns in Abkhazia are still quiet: the forgotten roots of a post-Soviet frozen conflict - CHELARU, Valeria (Studia Universitatis Babeș-Bolyai Historia, 2022)
This article re-evaluates Abkhazia's frozen conflict in light of the region's shared history with the Soviet Union. The article's primary purpose is to re-examine the role of politicized identities in the emergence and maintenance of frozen conflicts. Since macro perspectives on the frozen conflicts in the former Soviet space might not be entirely relevant to understanding such a mechanism, Abkhazia's case study provides us the opportunity to substantiate the post-imperial legacy's intricacies. To achieve that, the region's Soviet history, intrinsically linked to Soviet Union's political configuration, has been scrutinized. The impact of the Soviet policies on Abkhazia's engineering for political purposes is tackled in conjunction with the region's ethnic identity. Article history: Received: 24.05.2022; Revised 06.08.2022; Accepted: 06.08.2022; Available online: 15.09.2022 Rezumat: Articolul încearcă să reinterpreteze conflictul înghețat din Abkhazia în durata lungă a istoriei împărtăşite în Uniunea Sovietică. Pentru aceasta va fi reexaminat rolul jucat de identitățile politizate/bolşevizate în crearea şi menținerea conflictelor înghețate. Cum viziunile macro nu reuşesc să explice pe deplin acest mecanism, prin acest studiu de caz dedicat Abhkaziei încercăm să explicăm moştenirile imperiale postsovietice în lumina dezvoltărilor istorice din perioada comunistă în care ingineriile politice au afctat şi identitățile etnice. Cuvinte cheie: conflicte înghețate, Abkhazia, naționalism, identități, Uniunea Sovietică.